Assessment of soil chemical properties, available sulphur and micronutrients status of soils in Pune district of Maharashtra - SARAP, P.A.; HADOLE, S.S.; LAKHE, S.R.; DHULE, D. T.; PARMAR, J. N. (Journal of Soil and Water Conservation, 2020)
survey in 13 blocks of Pune District in Maharashtra was conducted on micro and secondary nutrients. The results obtained in the present study clearly showed a large variability in chemical properties of soil across the Pune district. The pH, EC, organic carbon and CaCO3 of soils varied from 6.34 to 8.89, 0.10 to 0.67 dS m-1, 1.63 to 9.80 g kg 1 and 2.13 to 14.0 percent, respectively. Results revealed that the 6.0, 56.9, 47.8, 5.9 and 15.7 per cent soil samples were found to be deficient in S, Zn Fe, Mn and B, respectively. None of the soil samples were found low in Cu. The nutrient index values are low for zinc (1.49), medium for iron (1.73), whereas high nutrient indices were observed for sulphur (2.58), manganese (2.65), copper (2.96) and boron (2.37). This information could aid in decision making for application of plant nutrients for higher monetary returns to the farmers and extension functionaries